Engineering Collariella virescens Peroxygenase for Epoxides Production from Vegetable Oil - Dolores Linde; Alejandro González-Benjumea; Carmen Aranda; Juan Carro; Ana Gutiérrez; Angel T. Martínez (MDPI AG, 2022)
Vegetable oils are valuable renewable resources for the production of bio-based chemicals and intermediates, including reactive epoxides of industrial interest. Enzymes are an environmentally friendly alternative to chemical catalysis in oxygenation reactions, epoxidation included, with the added advantage of their potential selectivity. The unspecific peroxygenase of Collariella virescens is only available as a recombinant enzyme (rCviUPO), which is produced in Escherichia coli for protein engineering and analytical-scale optimization of plant lipid oxygenation. Engineering the active site of rCviUPO (by substituting one, two, or up to six residues of its access channel by alanines) improved the epoxidation of individual 18-C unsaturated fatty acids and hydrolyzed sunflower oil. The double mutation at the heme channel (F88A/T158A) enhanced epoxidation of polyunsaturated linoleic and α-linolenic acids, with the desired diepoxides representing > 80% of the products (after 99% substrate conversion). More interestingly, process optimization increased (by 100-fold) the hydrolyzate concentration, with up to 85% epoxidation yield, after 1 h of reaction time with the above double variant. Under these conditions, oleic acid monoepoxide and linoleic acid diepoxide are the main products from the sunflower oil hydrolyzate.